(untitled) (Journal of Architectural Design, 2022)
Recently, a person has become a powerful relief-forming force. Drains and floods the territory, interferes with the life of the coast, creates mountains, pits, builds cities, changing the relief of the earth. This article considers the anthropogenic relief, i.e. relief created with the participation of man